1995
DOI: 10.1074/jbc.270.16.9407
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Induction of the Ubiquitin Conjugation Pathway Accompanies the Developmentally Programmed Death of Insect Skeletal Muscle

Abstract: The developmentally programmed cell death of abdominal intersegmental muscles in the tobacco hawk-moth Manduca sexta is coincident with a 10-fold induction of the polyubiquitin gene as a hormonally regulated event (Schwartz, L. M., Myer, A., Kosz, L., Engelstein, M., and Maier, C. (1990) Neuron 5, 411-419). Solid phase immunochemical assays measuring intersegmental muscle pools of free and conjugated ubiquitin reveal that the induction of polyubiquitin mRNA is accompanied by a proportional increase in total ub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(92 citation statements)
references
References 52 publications
(83 reference statements)
3
88
1
Order By: Relevance
“…Furthermore, mice deficient in IL-10, resulting in enhanced Th1 responses, succumbed to infection with an avirulent strain of Toxoplasma gondii, with markedly enhanced liver and lung necrosis (29,30). Numerous studies have also implicated ubiquitin in the proteolysis that accompanies apoptosis (31)(32)(33)(34). Although no gross necrosis was observed in the lung sections during this limited time period, the apparent activation of the cell cycle could be the organism's attempt to compensate for cells lost due to tissue damage.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, mice deficient in IL-10, resulting in enhanced Th1 responses, succumbed to infection with an avirulent strain of Toxoplasma gondii, with markedly enhanced liver and lung necrosis (29,30). Numerous studies have also implicated ubiquitin in the proteolysis that accompanies apoptosis (31)(32)(33)(34). Although no gross necrosis was observed in the lung sections during this limited time period, the apparent activation of the cell cycle could be the organism's attempt to compensate for cells lost due to tissue damage.…”
Section: Discussionmentioning
confidence: 89%
“…Emerging evidence suggests a role for the ubiquitin system in selective developmental processes (Pickart et al, 1989;Schwartz et al, 1990;Glotzer et al, 1991;Scotting et al, 1991;Muralidhar and Thomas, 1993;Haas et al, 1995). We have therefore taken the first systematic approach towards identifying and characterizing ubiquitin and its associated enzymes in early development using a single vertebrate animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated a role for ubiquitin in the degeneration of the intersegmental muscles (ISM) following pupation in the tobacco hawkmoth, Manduca sexta (Schwartz et al, 1990). Subsequently, it was revealed that a 10-fold increase in ISM ubiquitin-conjugate levels, under the regulation of glucocorticoid 20-hydroxyecdysone, is responsible for the ISM developmentally programmed cell death (Haas et al, 1995). Scotting et al (1991) described a limited study using chicken embryos in which ubiquitinated proteins were immunohistochemically detected in the cells of the lens, notochord, and myotome.…”
Section: Introductionmentioning
confidence: 99%
“…Hence proteolytic pathways involving both thiol proteases and perhaps ubiquitin conjugation appear to be active just before degeneration of specific cell types in anthers, suggesting a role for multiple proteolytic systems during anther cell death. The ubiquitin-dependent pathway of proteolysis is induced during pcd in degenerating insect muscles (Haas et al, 1995).…”
Section: Anther Dehiscencementioning
confidence: 99%